The Influence of Transactional Leadership on Organization Innovativeness (OI) Mediated by Organizational Learning Capability (OLC) in Medium Small Enterprise Kendari City - Thahira, Agniya; Tjahjono, Heru Kurnianto; Susanto, Susanto (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to explain the relationship between transactional leadership and organization innovativeness through organizational learning capability as a mediator. This research was conducted at UKM (Small and Medium Enterprises) in the City of Kendari, Southeast Sulawesi. The purposive sampling technique was applied in this study with 125 respondents. The findings in this study are that transactional leadership does not have a significant direct effect on organizational learning capability, but has a positive and significant direct effect on organization innovativeness. The results revealed that organizational learning capability has a very large positive and significant direct effect on organizational innovation, business organizations are expected to maximize their learning processes to create innovations to maintain and develop their existence in the future.